PENGARUH MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA TERHADAP HASIL BELAJAR SISWA PADA TEMA 3 SUBTEMA 1 KELAS V SD NEGERI 050629 TANJUNG LANGKAT - Br Ginting, Juni Reh Meita Br Ginting; Nurmayani, Nurmayani; Gultom, Ibrahim; Ananda, Lala Jelita; Afriadi, Putra (Jurnal Merah Putih Sekolah Dasar, 2023)
This research aims to determine the effect of student learning outcomes using multimedia-based learning media on Theme 3 Sub-theme 1 Class V at SD Negeri 050629 Tanjung Langkat FY 2022/2023. The research location was carried out at SD Negeri 050629 Tanjung Langkat, which consists of 2 classes, namely: Class VA (Experimental Class) and Class VB (Control Class). In class V A with a total of 20 students and class VB with a total of 20 students. The sample collection technique is Total Sampling, namely sample selection where the entire population is selected as the sample. This type of research is. The data collection tool used to determine learning outcomes is an objective test with 30 questions whose validity and reliability have been tested. From the analysis of data from 20 students in the experimental class and 20 students in the control class, the experimental class average was 53.75 for Pre-Test and 79.25 for Post-Test, while for the control class the average for Pre-Test was 42.2 and Post-Test. -Test 65.3. At the significant level x= 0.05. Both classes have a normal distribution because Lottable, namely 2.185>1.685. The author concludes that there is a significant influence from multimedia-based learning media on Theme 3 Subtheme 1 Class V at SD Negeri 050629 Tanjung Langkat FY 2022/2023. Keywords: Learning Outcomes, Multimedia Based Learning Media